Classroom applicability of blooms mastery learning as perceived by teachers - Hassan, Olusola (Universitas Negeri Yogyakarta, 2022)
This study investigated the applicability of mastery learning in public senior school as perceived by teachers. The study used descriptive survey research type. Two hundred and thirty teachers were sampled from public senior secondary schools in Kosofe local government area of Lagos. Teachers' perception on the applicability of Mastery Learning (TPABML) was designed by the researcher to measure teachers perception, the instrument was validated with reliability index of 0.74. Data collected was analysed using mean score, percentages and independent t-test of significance. Findings showed on the whole, teachers' perception does not favour the use of blooms mastery in public senior secondary. Result also showed significant difference between teachers with post-graduate qualification and teachers with Bachelor degree, but no significant difference was found based on teachers' experience. The result also finds no significant difference on the basis of gender. The study recommends that Government should re-orientate teachers to change their views and make efforts to apply mastery learning as it has recorded positive results.